Effect of Foreign Ownership on Financial Performance of Listed Firms in Nairobi Securities Exchange in Kenya - Ng’ang’a, Peter Ndungu; S. Namusonge, Prof. G.; Sakwa, Prof. M.M. (IJRDO - Journal of Business Management, 2016)
This study aimed to determine the effects of foreign ownership on firm’s financial performance of listed firms. The study findings indicated correlation co-efficient of 0.683, implying a positive relationship between foreign ownership and financial performance. This was evidenced by the p value of 0.000 which is less than that of critical value (0.05). The study concluded that there was a significant positive relationship between foreign ownership and firm’s financial performance.